Neonatal outcomes for pregnancies affected by haemolytic disease of the fetus and newborn and managed with intrauterine transfusion. (18th April 2012) - Birchenall, KA; Illanes, S; Overton, TG; Liebling, RE; Soothill, PW; Lopez, JF; Denbow, M
Abstract : Introduction: This study was conducted within the tertiary Fetal Medicine Unit (FMU) at St Michael's Hospital (StMH), Bristol. The first aim was to provide improved information regarding neonatal outcomes for parents of pregnancies affected by Haemolytic Disease of the Fetus and Newborn (HDFN) and managed by intrauterine transfusion (IUT). The second aim was to determine if a change in IUT protocol in 2004 had improved safety; including attendance of two FMU Consultants, use of fetal sedation, and use of the intrahepatic vein as an alternative route to placental cord insertion if deemed safer. Methods: Data for pregnancies affected by HDFN as a result of haemolytic red cell alloimmunisation and managed with IUT at StMH between 1999 and 2009 were retrospectively collected using local databases, and review of the medical notes. Results: 256 relevant IUTs were performed. The median number of IUTs per pregnancy was two. 91% of live deliveries had five minute APGAR scores ≥9. 98% were admitted to NICU/SCBU; requiring phototherapy (96%), exchange transfusion (36%) and top-up transfusion (30% immediate, 13% late). Following the change in protocol, there was a significant reduction in the number of emergency caesarean sections occurring directly after an IUT procedure (n=5vs0;p=0.02). 1% of IUTs resulted in fetal loss within 48 hours of IUT, none of which occurred under the new protocol (n=3vs0;p=0.08NS). Conclusions: Although the majority of neonates required admission to NICU/SCBU and phototherapy, the median-term outcomes were positive. Importantly, the safety of the IUT procedure has significantly improved since the change in protocol.